2008
DOI: 10.1590/s1984-29612008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of antibodies against Neospora caninum in stray and domiciled dogs from urban, periurban and rural areas from Paraná State, Southern Brazil

Abstract: RESUMOAnticorpos anti-Neospora caninum foram detectados pela reação de imunofluorescência indireta (RIFI), em cães errantes e domiciliados das áreas urbana, periurbana e rurais de Curitiba, estado do Paraná, Brasil. Do total de 556 cães, 18,17% (101) foram soropositivos para N. caninum (título de 1:50). A frequência de anticorpos foi de 12,71% nos cães urbanos, de 15,73% nos periurbanos e de 25,38% nos cães rurais. Nos cães rurais a frequência de anticorpos foi maior do que nos cães urbanos (P<0.05). Não houve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
4
0
4
Order By: Relevance
“…This result was similar to the findings from other studies conducted in Bahia and Paraná, which also did not find differences between owned and stray dogs (JESUS et al, 2006;FRIDLUND-PLUGGE et al, 2008). However, there have been reports of lower seroprevalence of N. caninum among owned dogs (AZEVEDO et al, 2005) and greater chances of infection among street dogs (GENNARI et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result was similar to the findings from other studies conducted in Bahia and Paraná, which also did not find differences between owned and stray dogs (JESUS et al, 2006;FRIDLUND-PLUGGE et al, 2008). However, there have been reports of lower seroprevalence of N. caninum among owned dogs (AZEVEDO et al, 2005) and greater chances of infection among street dogs (GENNARI et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Antibodies against N. caninum have also been observed in dogs without neurological signs. Hence, simply the presence of antibodies does not indicate clinical neosporosis (AZEVEDO et al, 2005;VÁCLAVEK et al, 2007;FRIDLUND-PLUGGE et al, 2008). On the other hand, in cases of seronegative dogs or dogs with small titers, neosporosis should not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…For dogs living in stray situation in Brazil, as neighborhood dogs, the seroprevalence for Leishmania spp. have been ranging from 0.0027% to 32.5% (FREHSE et al, 2010;SEABRA et al, 2015;TRONCARELLI et al, 2009;VALADAS et al, 2010), for T. gondii from 31.6% to 68.4% (MEIRELES et al, 2004;SEABRA et al, 2015;SOUZA et al, 2003;VALADAS et al, 2010), for T. cruzi from 2.0% to 4.0% (MORAIS et al, 2013;TRONCARELLI et al, 2009) and for N. caninum from 3.2% to 22.1% (FRIDLUND-PLUGGE et al, 2008;SEABRA et al, 2015;SOUSA et al, 2012;VALADAS et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated a wide prevalence of antibodies against both parasites in several locations of Brazil, usually up to 10.0% (Cañón-Franco et al , 2003; Meireles et al , 2004; Andreotti et al , 2006; Collantes-Fernández et al , 2008; Figueredo et al , 2008; Fridlund-Plugge et al , 2008; Locatelli-Dittrich et al , 2008; Benetti et al , 2009; Guimarães et al , 2009; Silva et al , 2010; Valadas et al , 2010). In most of these studies the prevalence for T. gondii antibodies are higher than for N. caninum , indicating a higher exposure of dogs by this parasite.…”
mentioning
confidence: 98%